Proceedings of the 13th ACM Conference on Recommender Systems 2019
DOI: 10.1145/3298689.3346985
|View full text |Cite
|
Sign up to set email alerts
|

Personalized diffusions for top-n recommendation

Abstract: This paper introduces PerDif; a novel framework for learning personalized difusions over item-to-item graphs for top-n recommendation. PerDif learns the teleportation probabilities of a timeinhomogeneous random walk with restarts capturing a user-specifc underlying item exploration process. Such an approach can lead to signifcant improvements in recommendation accuracy, while also providing useful information about the users in the system. Per-user ftting can be performed in parallel and very efciently even in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…From a user modeling point of view this translates to the implicit assumption that every user explores the itemspace in exactly the same way-overlooking the reality that different users can have different behavioral patterns. The fundamental premise of PerDif [57] is that the latent item exploration behavior of the users can be captured better by user-specific preference propagation mechanisms; thus, leading to improved recommendations.…”
Section: User-adaptive Diffusion Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…From a user modeling point of view this translates to the implicit assumption that every user explores the itemspace in exactly the same way-overlooking the reality that different users can have different behavioral patterns. The fundamental premise of PerDif [57] is that the latent item exploration behavior of the users can be captured better by user-specific preference propagation mechanisms; thus, leading to improved recommendations.…”
Section: User-adaptive Diffusion Modelsmentioning
confidence: 99%
“…Leveraging the special properties of the stochastic matrix G the above non-linear optimization problem can be solved efficiently. In particular, it can be shown [57] that the optimization problem ( 59) is equivalent to minimize…”
Section: User-adaptive Diffusion Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotions such as happiness (Fowler and Christakis 2008) and hatefulness (Ribeiro et al 2018) have also been observed to spread through social networks. These processes, known as information diffusion, have traditionally been studied in the social sciences (Granovetter 1978), but more recently have motivated applications in viral marketing (Kempe, Kleinberg, and Tardos 2003) and recommender systems (Nikolakopoulos et al 2019). Many models exist that capture the diffusion process, including epidemic models (Kermack and McKendrick 1927), voter models (Clifford and Sudbury 1973), the Independent Cascade (Kempe, Kleinberg, and Tardos 2003), and the Linear Threshold Model (LTM) (Granovetter 1978).…”
Section: Introductionmentioning
confidence: 99%